PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA BANK PERKREDITAN RAKYAT - Maria Niken Setyarini; Anastasia Susty Ambariani (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2014)
This study aim to examine the efect of budget participation on managerial performance and organizational commitment as an intervening variable in Rural Bank in Yogyakarta. This study using path analysis. Results from this study indicate that budgetary participation infuence on organizational commitment. In addition, variable proven organizational commitment as an intervening variable between budgetary participation and managerial performance.Keywords: Budget Participation, Organizational Commitment, Managerial Performance